1996
DOI: 10.1016/s0002-9394(14)70411-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin A antibodies against Pseudomonas aeruginosa in the tear fluid of contact lens wearers

Abstract: %Purpose. Pseudomonas aeruginosa is the most im portant cause of contact lens-associated ulcera tive keratitis, especially for those who use extended-wear lenses. U ntil now, the presence of specific anti-P. aeruginosa im m unoglobulin A (IgA) antibodies in the tears of contact lens wearers has n o t been investigated an d is the purpose of the current study. M ethods.T h e levels o f specific IgA antibodies against P. aeruginosa and total secretory IgA (sIgA) concentrations were m easured in tears o f various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Tear sIgA levels have been found to be decreased in some studies (Lan et al, 1999; Pearce et al, 1999; Vinding et al, 1987), unchanged (Temel et al, 1991b) and increased with RGP wear, although this normalized by one year of lens wear (Kijlstra et al, 1992; Temel et al, 1991b). Notably in one study, Pseudomonas specific IgA was lower in contact lens wearers although the levels of total sIgA were not different between lens wearers and controls (Cheng et al, 1996). Two studies reported no change in tear sPLA 2 (Hume et al, 2004; Yamada et al, 2006) whereas a third reported a decrease with lens wear (Aho et al, 2003).…”
Section: Modulation Of Tear Antimicrobialsmentioning
confidence: 99%
“…Tear sIgA levels have been found to be decreased in some studies (Lan et al, 1999; Pearce et al, 1999; Vinding et al, 1987), unchanged (Temel et al, 1991b) and increased with RGP wear, although this normalized by one year of lens wear (Kijlstra et al, 1992; Temel et al, 1991b). Notably in one study, Pseudomonas specific IgA was lower in contact lens wearers although the levels of total sIgA were not different between lens wearers and controls (Cheng et al, 1996). Two studies reported no change in tear sPLA 2 (Hume et al, 2004; Yamada et al, 2006) whereas a third reported a decrease with lens wear (Aho et al, 2003).…”
Section: Modulation Of Tear Antimicrobialsmentioning
confidence: 99%
“…Comparisons between studies of tear sIgA are not always possible due to the range of methodologies used, subject groups, CL types and wear schedule differences. A recent report has shown that the tears of CL wearers have decreased levels of sIgA specific for the pathogen Pseudomonas aeruginosa (23). The significance of reduced levels of sIgA is speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-1 (IL-1) and inally the migration of Polymorphonuclear leukocytes cells (PMNs) to the cornea to get rid of the pathogen, the low or entry of PMNs cells due to the induction of cytokines that attract these cells, that is, the damage resulting from keratitis by bacteria caused by the factors associated With bacterial settlement, this also results from the response of PMNs cells (Cheng et al, 1996). As a result of the host's in lammatory response to bacterial corneal infection, the response is at the beginning of the entry of PMNs cells that cause corneal tissue breakdown, although it mainly analyzes the injury, as PMNs migrate from the lacrimal membrane and from the iris and peripheral vessels to the areas of the vascular cornea (Hobden et al, 1999;Thakur et al, 2004).…”
Section: Immune Changes Associated With Corneal Infection In Paerugimentioning
confidence: 99%